Isolation of the promoter region of the FaPAL2 gen of Fragaria x ananassa Cv. “Camino Real” and evaluation of it’s functionality in response to UV-C irradiation - Masís-Ramos, Stephannie (2021)
The phenylalanine ammonium lyase protein or PAL is a key enzyme in the pathway of flavonoid synthesis; in strawberry 6 genes have been reported that encode it, including FaPAL2. Flavonoids are essential secondary metabolites for protection against UV light in plants, furthermore, they are of great pharmaceutical interest due to their antioxidants, antibacterial, anti-inflammatory, antimutagenic and anticancer properties. Increase in flavonoid compounds in strawberries irradiated with UV-C light has been correlated with high levels of FaPAL gene expression. In order to study and control the expression of genes of interest, it is indispensable to know the promoters functionality, so the present investigation aimed to identify and isolate the FaPal2 gene promoter using the TAIL PCR technique, to later assess its activity upon response to UV-C light in Fragaria x ananassa cv. “Camino Real” fruits via Agrobacterium tumefaciens using the GUS reporter gene. The promoter of the FaPAL2 gene was successfully isolated and sequenced, and later used to generate a genetic construct and evaluate its transient genetic expression in agro-infiltrated strawberry fruits. A positive histological staining was identified in the agro-infiltrated fruits, both irradiated and non-irradiated, indicating that the FaPAL2 gene promoter acts positively in response to UV-C light, but not in an exclusive manner.